The Expression of Attitude to Learning among Participants of Chemistry Olympiads - Kurienė, Almeda (Acta Paedagogica Vilnensia, 2001)
The aim of this paper is to evaluate the progress and attitude to learning chemistry among Olympiad’s participants. The research was conducted among the participants of 33th Lithuanian Pupils' Olympiad of Chemistry which took place in April, 2000. On the basis of this research it can be concluded that the knowledge in principal subjects (mathematics, physics, foreign language and Lithuanian) of 51,28% of participants is graded 7-10 points and that of chemistry is graded 9-10. 98,29% of participants consider chemistry to be their favourite subject and exact and natural sciences to be more interesting than humanitarian ones. A successful learning of chemistry is determined by pupils• aim to understand nature phenomena properly and to gain better knowledge of chemistry. Good chemistry learning results directly influence students' choice of their way of life. 56,92% of the Olympiad participants are planning to study chemistry or other subjects related with it.
Keywords: students' progress; teaching subjects; senior students; vocational education; chemistry olympiads.